1957
DOI: 10.1111/j.1467-6494.1957.tb01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Aspects of Beliefs About Men and Women

Abstract: IN A PREVIOUS paper (3) we demonstrated that among college students at the Umversity of California both men and women esteem men significantly more highly than women In the present report we make a qualitative examination of the characteristics which men and women ascribe to themselves and to each other What are the characteristics that men and women attribute to the two sexes ? How do traits ascribed to men or women "m general" compare with those applied by men and women to themselves as mdividuals'' Can the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
4

Year Published

1973
1973
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(27 citation statements)
references
References 3 publications
1
21
0
4
Order By: Relevance
“…In general, women tend to be viewed as gentle, warm and passive, whereas men are perceived as tough and aggressive (Best & Williams, 1990;Eagly & Steffen, 1984;Sheriffs & McKee, 1957). These stereotypes may be used to evaluate individuals, such that those perceived to be more feminine (possessing more traits stereotypically associated with women) are viewed differently than those who are perceived to be more masculine (having more traits associated with the stereotype of men).…”
Section: Gender Stereotypesmentioning
confidence: 95%
“…In general, women tend to be viewed as gentle, warm and passive, whereas men are perceived as tough and aggressive (Best & Williams, 1990;Eagly & Steffen, 1984;Sheriffs & McKee, 1957). These stereotypes may be used to evaluate individuals, such that those perceived to be more feminine (possessing more traits stereotypically associated with women) are viewed differently than those who are perceived to be more masculine (having more traits associated with the stereotype of men).…”
Section: Gender Stereotypesmentioning
confidence: 95%
“…Gender stereotypes, in particular, refer to those characteristics often associated with men or women, and are thought of as gender specific (i.e., exclusively male or exclusively female). Several early studies revealed that gender stereotypes were consistently maintained and exceedingly conventional (Fernberger, 1948; Kirkpatrick, 1936; Sheriffs & McKee, 1957). Half a century later, findings suggest that gender stereotypes still are prevalent (e.g., Krueger, Hasman, Acevedo, & Villano, 2003; Sczesny, Spreemann, & Stahlberg, 2006).…”
mentioning
confidence: 99%
“…One of the earliest programs of research to examine gender stereotypes was conducted by McKee and Sheriffs in the USA in the 1950s , 1959Sheriffs and McKee 1957). Using a list of 200 adjectives, they found a large number of characteristics differentially ascribed to men in general and women in general.…”
Section: Early Gender Researchmentioning
confidence: 99%